COMPARISON STUDY OF ANTIOXIDANT ACTIVITY FROM THREE BANANA LEAVES EXTRACTS - Ratna Handayani; Kinkstie Fans; Titri Siratantri Mastuti; Dela Rosa (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2021)
Banana (Musa spp.) is mainly grown in the tropical and subtropical countries. Previous study reported that Musa spp. leaves had a potential antioxidant activity, but it was still rarely studied further. In this research, leaves of Musa balbisiana, Musa acuminate, and Musa paradisiaca were extracted using maceration method for 24 hours with three kinds of solvent having different polarities: ethanol (polar), ethyl acetate (semi polar), and hexane (nonpolar). The goal of this research was to compare and determine the stability of the antioxidant activity extracted from different Musa sp. leaves. The highest antioxidant activity is found from Musa balbisiana leaves extract with IC50 value 340.07±22.54 ppm (hexane fraction). Correlation analysis between antioxidant activity, total phenolic content, and total flavonoid of the extracts cannot conclude that the active antioxidant substances in these three banana species leaves were from phenolic or flavonoid groups. This crude extract from Musa balbisiana was then subjected to various pH levels (3.0, 5.0, 7.0, and 9.0) and temperatures (50, 70, and 90°C) to determine the stability of its antioxidant activity. It is found that the best stability condition is at pH 3.0 and temperature of 50°C with an increase of 63.1% in IC50, a decrease of 15.72% in total phenolics, and a decrease of 3.67% in total flavonoids as compared to before treatment.